Licensing of Private Pesticide Applicators in Florida - Frederick M. Fishel (EDIS)
PI-149, a 4-page fact sheet by Frederick M. Fishel, explains the licensing and regulation of persons who apply restricted use pesticides to agricultural commodities in Florida. Published by the UF Pesticide Information Office, February 2007.